Water resources and environmental change in a Mediterranean environment: The south-west sector of the Duero river basin (Spain) - Ceballos-Barbancho, Antonio; Morán-Tejeda, Enrique; Luengo-Ugidos, Miguel Ángel; Llorente-Pinto, José Manuel (Journal of Hydrology, 2008)
In the present work we analyse the temporal trend of water supplies to a network of basins, representative of the Mediterranean climate and plant cover, and its relationship with the evolution of temperatures, precipitation, and the changes that have occurred in the plant cover with time. The results point to an important decrease in water supply, with a high degree of dependence on precipitation (r = 0.85; p-value < 0.001). Important changes are also seen in the monthly distribution of water discharges due to modiﬁcations that have occurred in the intra-annual distribution of precipitation and an increase in temperatures in spring and summer. The rivers studied are losing their snow regime, with very important reductions in the winter and spring discharges. The results show that to date the changes detected in the forest have not affected the water discharges of the rivers. This absence of effect is probably because the changes observed in the plant cover are currently below the threshold after which it is possible to detect the effect of the forest on water discharges and because the interannual variability in rainfall and discharge in Mediterranean environments is so high that it masks other time-dependent changes. The planning and management of water resources should take these changes into consideration with respect to the functioning of hydroclimatic systems
Keywords: Duero river; Environmental change; Headwaters; Mediterranean; Precipitation; Water discharge

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability